2009
DOI: 10.1038/ng.447
|View full text |Cite
|
Sign up to set email alerts
|

IL28B is associated with response to chronic hepatitis C interferon-α and ribavirin therapy

Abstract: Hepatitis C virus (HCV) infects 3% of the world's population. Treatment of chronic HCV consists of a combination of PEGylated interferon-alpha (PEG-IFN-alpha) and ribavirin (RBV). To identify genetic variants associated with HCV treatment response, we conducted a genome-wide association study of sustained virological response (SVR) to PEG-IFN-alpha/RBV combination therapy in 293 Australian individuals with genotype 1 chronic hepatitis C, with validation in an independent replication cohort consisting of 555 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

100
1,519
13
42

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,721 publications
(1,680 citation statements)
references
References 46 publications
100
1,519
13
42
Order By: Relevance
“…Thompson et al 8 reanalyzed the patient population from Ge et al 3 on an Tanaka et al 4 No. of patients 314 T/T 64** T/G 13 G/G 0 Suppiah et al 5 No. of patients 848 T/T 56 † † T/G 36 G/G 31…”
Section: Predictive Endpoints Of Il28b Snpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thompson et al 8 reanalyzed the patient population from Ge et al 3 on an Tanaka et al 4 No. of patients 314 T/T 64** T/G 13 G/G 0 Suppiah et al 5 No. of patients 848 T/T 56 † † T/G 36 G/G 31…”
Section: Predictive Endpoints Of Il28b Snpsmentioning
confidence: 99%
“…[3][4][5] The three genes encode IFN-k1 (IL29), IFN-k2 (IL28A), and IFN-k3 (IL28B). The same set of SNPs was subsequently associated with natural clearance of HCV.…”
mentioning
confidence: 99%
“…Genetic and functional studies have identified key molecules and processes involved in clearing HCV spontaneously and using interferon (IFN)‐α based therapies 3, 4, 5, 6, 7, 8, 9. These studies have implicated both innate and adaptive mechanisms in clearing HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most impressive findings from Gene Wide Association Studies (GWAS) to date has been the identification of single nuclear polymorphisms (SNPs) upstream of IFN‐λ3 which are protective against HCV chronicity and treatment failure 3, 4, 5, 6, 7. This has been fine mapped to the TT/‐G polymorphism at rs67272382 in a CpG island, which is in strong linkage disequilibrium with IFN‐λ3 and is most likely to be the causal variant, with the possibility of defining a new type 3 IFN, IFN‐λ4 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies have recently identified genetic variations near the IL28B gene, encoding for interferon (IFN)-k3, as a strong predictor of spontaneous and treatment-induced clearance of hepatitis C infection [13][14][15][16][17][18]. Protective variants at the rs12979860 and rs8099917 loci have consistently been associated with faster decline in viral load and an approximately twofold higher sustained virologic response rate during standard of care treatment, particularly, in patients affected by the difficult to cure HCV genotypes 1 and 4 [19,20].…”
mentioning
confidence: 99%